Genetic counselling in a national referral centre for pulmonary hypertension. Issue 2 (23rd December 2015) - Girerd, Barbara; Montani, David; Jaïs, Xavier; Eyries, Mélanie; Yaici, Azzedine; Sztrymf, Benjamin; Savale, Laurent; Parent, Florence; Coulet, Florence; Godinas, Laurent; Lau, Edmund M.; Tamura, Yuichi; et al.
Genetic causes of pulmonary arterial hypertension (PAH) and pulmonary veno-occlusive disease (PVOD) have been identified, leading to a growing need for genetic counselling. Between 2003 and 2014, genetic counselling was offered to 529 PAH and 100 PVOD patients at the French Referral Centre for Pulmonary Hypertension. Mutations in PAH-predisposing genes were identified in 72 patients presenting as sporadic PAH (17% of cases; 62 mutations in BMPR2, nine in ACVRL1 ( ALK1 ) and one in ENG ) and in 94 patients with a PAH family history (89% of cases; 89 mutations in BMPR2, three in ACVRL1 ( ALK1 ) and two in KCNK3 ). Bi-allelic mutations in EIF2AK4 were identified in all patients with a family history of PVOD (n=19) and in seven patients (8.6%) presenting as sporadic PVOD. Pre-symptomatic genetic diagnosis was offered to 272 relatives of heritable PAH patients, identifying mutations in 36.4% of them. A screening programme is now offered to asymptomatic mutation carriers to detect PAH in an early phase and to identify predictors of outcomes in asymptomatic BMPR2 mutation carriers. BMPR2 screening allowed us to offer pre-implantation diagnosis to two couples with a BMPR2 mutation. Genetic counselling can be implemented in pulmonary hypertension centres. Genetic causes of PAH and PVOD have been identified; genetic counselling can be implemented in PH centres http://ow.ly/TLbee